Stress in rearing: Biochemical and growth impacts of acoustic exposure in juvenile Dicentrarchus labrax - M. Mauro; P. Giner-Tarazona; V. Espinosa; V. Puig-Pons; S. Morell-Monzó; M. Vazzana; F. Longo; R. De Luca; J. Ramis; P. Poveda; J. Carbajo; I. Pérez-Arjona (Marine Pollution Bulletin, 2026)

Multiple Eurasian Origins and Admixture Shaped the Genomic Legacy of the House Mouse Invasion in Africa - Daniel Poveda‐Martinez; Philippe Gauthier; Margaux J. M. Lefebvre; Fanny Degrugillier; Gauthier Dobigny; Jean‐Pierre Quéré; Ambroise Dalecky; Youssoupha Niang; Mamadou Kane; Clark Mbou‐Boutambe; Joa Mangombi; Solimane Ag Atteynine; et al. (Molecular Ecology, 2026)
Commensal mammals offer unique opportunities to study how human‐mediated dispersal, admixture, and secondary contact shape genomic variation during range expansion, yet for one of the most successful invasive commensals globally, the western house mouse Mus musculus domesticus , invasion dynamics across Africa remain largely unexplored. Here, we present a large‐scale population genomic analysis of 380 whole‐genome sequences, including 303 newly sequenced low‐coverage genomes, of which 216 are from 13 distinct African populations, enabling us to investigate how human‐mediated dispersal and secondary contact with native species shape the genomic legacy of a commensal mammal invasion. Ancestry analyses reveal contributions from at least three major Eurasian source lineages contributing to African populations: an Iberian–West Asian lineage present in Morocco, Algeria, and Niger; a Mediterranean lineage represented in Tunisia; and a Northern European lineage dominant in West and Central Africa. Demographic inferences indicate both recent and ancient episodes of divergence and population contraction. In West and Central Africa, divergence times broadly overlap with European maritime expansion and colonial trade. In contrast, North African populations exhibit older coalescent signals, consistent with early participation in the western Mediterranean radiation. We also detect substantial introgression from the native Mus spretus into North African populations in regions of sympatry. Collectively, our results reveal that the African invasion of the house mouse was not a single demographic process but a mosaic of population‐specific histories shaped by multiple introductions, shifting connectivity through time, admixture, and interspecific gene flow. These findings reinforce the importance of population‐level perspectives in invasion genomics, especially for commensal mammals whose dispersal is closely tied to human movement, and establish the most extensive open genomic resource for wild African house mice.

Impact of ground motion record selection on higher-mode responses in RC wall buildings: comparing uniform hazard and conditional spectra approaches - Jose Poveda; Gerard J. O’Reilly (Bulletin of Earthquake Engineering, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Biological control of damping-off by Fusarium oxysporum and F. verticillioides on pine and oak seedlings using edible ectomycorrhizal fungi - Jorge Poveda; Jorge Martín-García; Paula Zamora-Brauweiler; Mónica Pastor; Julio J. Díez (Pedobiologia, 2024)

Relation between morphology and native climate in the resistance of different Pinus pinaster populations to pitch canker disease caused by Fusarium circinatum - Raquel Díaz; Jorge Poveda; Esteban Torres-Sánchez; Tamara Sánchez-Gómez; Jorge Martín-García; Julio J. Diez (Forest Ecology and Management, 2024)

Precipitation over northern South America and the far‐eastern Pacific during ENSO : Phase synchronization at inter‐annual time scales - Hernán D. Salas; Alejandro Builes‐Jaramillo; Niklas Boers; Germán Poveda; Óscar J. Mesa; Jürgen Kurths (International Journal of Climatology, 2024)
We investigated the influence of the El Niño‐Southern Oscillation (ENSO) on inter‐annual precipitation variability in the far‐eastern Pacific (FEP) and northern South America (NSA) using an approach based on phase synchronization (PS). First, we carried out a detailed analysis of observational data to define the inter‐annual variability, eliminate the seasonal residual frequencies in hydro‐climatic anomalies, and assess the statistical significance of PS. Additionally, we characterized the seasonality of regional patterns of sea surface temperature, surface pressure levels, low‐level winds and precipitation anomalies associated with the ENSO states. We found that the positive (negative) precipitation anomalies experienced in the FEP and NSA differ from those previously reported in the literature. In particular, the Guianas (northeastern Amazon) and the Caribbean constitute two regions with negative (positive) rainfall anomalies during El Niño (La Niña), separated by a zone of non‐significant anomalies along the Orinoco Low‐level Jet corridor. Moreover, we showed that the ENSO signal is phase‐locked with inter‐annual rainfall and low‐level wind variability in most of the study regions. Furthermore, we found consistency in the PS between the Central and Eastern Pacific El Niño indices and hydroclimatic anomalies over the Pacific. However, some areas exhibited PS, although they did not show significant precipitation anomalies, suggesting that the influence of ENSO on tropical climatology manifests not only in terms of the magnitude of anomalies but also in terms of the phases only. Our approach advances the understanding of climatic anomalies in tropical regions and provides new insights into the non‐linear interactions between ENSO and hydroclimatic processes in tropical Americas.

Relationships between rhizosphere microbiota and forest health conditions in Pinus pinaster stands at the Iberian Peninsula - Carmen Morales-Rodríguez; Jorge Martín-García; Francisco J. Ruiz-Gómez; Jorge Poveda; Julio J. Diez (Applied Soil Ecology, 2024)

Beetroot juices as colorant in plant-based minced meat analogues: Color, betalain composition and antioxidant activity as affected by juice type - Juana Fernández-López; Angel J. Ponce-Martínez; Judith Rodríguez-Párraga; Ana M. Solivella-Poveda; Jose A. Fernández-López; Manuel Viuda -Martos; Jose A. Pérez-Alvarez (Food Bioscience, 2023)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Ground validation of TRMM 3B43 V7 precipitation estimates over Colombia. Part I: Monthly and seasonal timescales - Sara M. Vallejo‐Bernal; Viviana Urrea; Juan M. Bedoya‐Soto; Daniela Posada; Alejandro Olarte; Yadira Cárdenas‐Posso; Franklyn Ruiz‐Murcia; María T. Martínez; Walter A. Petersen; George J. Huffman; Germán Poveda (International Journal of Climatology, 2021)
In this study, we validate precipitation estimates remotely sensed by the Tropical Rainfall Measuring Mission (TRMM) at monthly and seasonal timescales, during the period 1998–2015, by calculating and analyzing diverse error metrics between the 3B43 V7 product and in situ measurements from 1,180 rain gauges over Colombia, of which at least 987 are fully independent of TRMM. We explore the existence of spatiotemporal patterns to assess the performance of 3B43 V7 over the five major natural regions of Colombia: Caribbean, Pacific, Andes, Orinoco and Amazon. The results show that 3B43 V7 product is able to capture the phase of the annual cycle of monthly mean precipitation, but the performance is not good for the amplitude, in particular over the Andes and Pacific regions owing to complex climatic and topographic conditions. In general, 3B43 V7 exhibits good performance in the low‐lying and plain Amazon, Orinoco and Caribbean regions. Over the Andes region, characterized by complex topography, overestimation errors are identified [root mean squared error (RMSE) ≥83.59 mm·month −1 and relative bias (BIAS) ≥4.69%], whereas the extremely wet rainfall regime of the Pacific region is largely underestimated (RMSE ≥253.52 mm ·month −1 and BIAS ≤−11.75%). These errors are greater during the wet seasons when the metrics reach worse scores than those reported in similar studies worldwide. Occurrence analyses showed that 3B43 V7 misses very frequent light rainfall events and less frequent but very heavy storms, which contribute to the overall underestimation (overestimation) observed over the Pacific (Andes) region. The error characteristics identified and quantified in this study confirm the well‐documented limitations of remote precipitation sensing and constitute a warning about major challenges that complex climatic and physiographic features can impose on satellite rainfall missions.

Diversity and Phenology of Wild Bees in a Highly Disturbed Tropical Dry Forest “Desierto de la Tatacoa”, Huila–Colombia - C A Poveda-Coronel; D Riaño-Jiménez; J R Cure (Neotropical Entomology, 2018)

Limitations of Water Resources Infrastructure for Reducing Community Vulnerabilities to Extremes and Uncertainty of Flood and Drought - Dena W. McMartin; Bruno H. Hernani Merino; Barrie Bonsal; Margot Hurlbert; Ricardo Villalba; Olga L. Ocampo; Jorge Julián Vélez Upegui; Germán Poveda; David J. Sauchyn (Environmental Management, 2018)

A global synthesis of the effects of diversified farming systems on arthropod diversity within fields and across agricultural landscapes - Elinor M. Lichtenberg; Christina M. Kennedy; Claire Kremen; Péter Batáry; Frank Berendse; Riccardo Bommarco; Nilsa A. Bosque‐Pérez; Luísa G. Carvalheiro; William E. Snyder; Neal M. Williams; Rachael Winfree; Björn K. Klatt; et al. (Global Change Biology, 2017)
Agricultural intensification is a leading cause of global biodiversity loss, which can reduce the provisioning of ecosystem services in managed ecosystems. Organic farming and plant diversification are farm management schemes that may mitigate potential ecological harm by increasing species richness and boosting related ecosystem services to agroecosystems. What remains unclear is the extent to which farm management schemes affect biodiversity components other than species richness, and whether impacts differ across spatial scales and landscape contexts. Using a global metadataset, we quantified the effects of organic farming and plant diversification on abundance, local diversity (communities within fields), and regional diversity (communities across fields) of arthropod pollinators, predators, herbivores, and detritivores. Both organic farming and higher in‐field plant diversity enhanced arthropod abundance, particularly for rare taxa. This resulted in increased richness but decreased evenness. While these responses were stronger at local relative to regional scales, richness and abundance increased at both scales, and richness on farms embedded in complex relative to simple landscapes. Overall, both organic farming and in‐field plant diversification exerted the strongest effects on pollinators and predators, suggesting these management schemes can facilitate ecosystem service providers without augmenting herbivore (pest) populations. Our results suggest that organic farming and plant diversification promote diverse arthropod metacommunities that may provide temporal and spatial stability of ecosystem service provisioning. Conserving diverse plant and arthropod communities in farming systems therefore requires sustainable practices that operate both within fields and across landscapes.

Genetic analysis based on plastidial and ribosomal sequences of the endemic bi-edaphic taxon Jurinea pinnata (Lag.) DC. (Compositae) in the Guadix-Baza Basin - E. Salmerón-sánchez; F. J. Pérez-García; J. M. Medina-Cazorla; M. I. Martínez-Nieto; F. Martínez-Hernández; J. A. Garrido-Becerra; A. J. Mendoza-Fernández; M. E. Merlo Calvente; J. F. Mota Poveda (Plant Biosystems, 2015)

Biogeography of the Baetic ranges (SE Spain): A historical approach using cluster and parsimony analyses of endemic dolomitophytes - J. M. Medina‐Cazorla; J. A. Garrido‐Becerra; A. Mendoza Fernández; F. J. Pérez‐García; E. Salmerón; C. Gil; J. F. Mota Poveda (Plant Biosystems, 2010)

Protein and Antigenic Variability among Mycoplasma hyopneumoniae Strains by SDS-PAGE and Immunoblot - P. Assunção; C. De la Fe; A. S. Ramírez; O. González Llamazares; J. B. Poveda (Veterinary Research Communications, 2005)

The Occurrence of Mycoplasmas in the Lungs of Swine in Gran Canaria (Spain) - P. Assunça˜o; C. De la Fe; B. Kokotovic; O. González; J. B. Poveda (Veterinary Research Communications, 2005)

Cluster of Leptospirosis Cases Among Children in France - Sertour N.; Menouard M.; Poveda J.; Perra A.; Baranton G.; Postic D. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Disseminated Histoplasmosis Successfully Treated with Liposomal Amphotericin B Following Azathioprine Therapy in a Patient from a Nonendemic Area - F. Poveda; J. García-Alegría; M. A. de las Nieves; E. Villar; N. Montiel; A. del Arco (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Disseminated histoplasmosis successfully treated with liposomal amphotericin B following azathioprine therapy in a patient from a nonendemic area - F. Poveda; J. García-Alegría; M. A. Nieves; E. Villar; N. Montiel; A. Arco (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Effect of the Nature of Exogenous Organic Matter on Pesticide Sorption by the Soil - E. Iglesias-Jiménez; E. Poveda; M. J. Sánchez-Martín; M. Sánchez-Camazano (Archives of Environmental Contamination and Toxicology, 1997)